2014
DOI: 10.1016/j.nicl.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cortical haemodynamics during neonatal seizures using diffuse optical tomography: A case study

Abstract: Seizures in the newborn brain represent a major challenge to neonatal medicine. Neonatal seizures are poorly classified, under-diagnosed, difficult to treat and are associated with poor neurodevelopmental outcome. Video-EEG is the current gold-standard approach for seizure detection and monitoring. Interpreting neonatal EEG requires expertise and the impact of seizures on the developing brain remains poorly understood. In this case study we present the first ever images of the haemodynamic impact of seizures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 71 publications
0
68
0
Order By: Relevance
“…Austin et al 32 employed a custom-made helmet with whole-head coverage, made of an outer shell of thermoplastic and an inner part of NIR-absorbing foam. Crucially, in all these DOT studies, the length of registration did not exceeded 2 h, with a minimal length of 60 min 6,14 up to a maximum of 115 min 13 and the gestational age ranged from 34 weeks gestation 13 to term. Here, we showed that the adoption of our hand-made cap (NeoCAP) enabled a safe continuous DOT monitoring for a 7-day period in a very preterm infant.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Austin et al 32 employed a custom-made helmet with whole-head coverage, made of an outer shell of thermoplastic and an inner part of NIR-absorbing foam. Crucially, in all these DOT studies, the length of registration did not exceeded 2 h, with a minimal length of 60 min 6,14 up to a maximum of 115 min 13 and the gestational age ranged from 34 weeks gestation 13 to term. Here, we showed that the adoption of our hand-made cap (NeoCAP) enabled a safe continuous DOT monitoring for a 7-day period in a very preterm infant.…”
Section: Discussionmentioning
confidence: 87%
“…6,13,[25][26][27][28][29][30][31] Prior studies in this field have raised the issue related to the cap tolerance by the neonates as a possible factor limiting the duration of DOT data acquisition. Singh et al 6 and Chalia et al 13 adopted a soft and flexible cap (EasyCap, Germany, i.e., our outer layer), with a whole-head coverage for a multimodal DOT-EEG acquisition. Ferradal and colleagues 14 employed a custom-made optode holder, composed of five triangular patches joined together with a neoprene headband, fixed to the head via Velcro straps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the development of non-destructive evaluation (NDE) based on optical tomography method has been focused on medical application [4,6,8,9]. Nevertheless, NDE OT development on other application is also interesting and promising as described by some researcher on this field [3,14].…”
Section: Introductionmentioning
confidence: 99%